2024
DOI: 10.3390/met14040451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Deformation and Heat Treatment on the Microstructure and Properties of Spray-Formed Al-Zn-Mg-Cu Alloys

Lingfei Cao,
Xiaomin Lin,
Zhenghao Zhang
et al.

Abstract: Spray forming is a manufacturing process that enables the production of high-performance metallic materials with exceptional properties. Due to its rapid solidification nature, spray forming can produce materials that exhibit fine, uniform, and equiaxed microstructures, with low micro-segregation, high solubility, and excellent workability. Al-Zn-Mg-Cu alloys have been widely used in the aerospace field due to their excellent properties, i.e., high strength, low density, and outstanding machinability. The allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 153 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…were performed under conditions of 470 °C/2 h of solution temperature and 120 °C of artificial aging, and, in order to learn more about the formation tendency of the GP zone, which is the nucleation site of the η' phase, the region between 0 and 1 h was enlarged and is shown in Figure 1. The heat treatment conditions used in the calculation were the commonly performed T6 heat treatment conditions for Al-Mg-Zn-Cu-based aluminum alloys [14][15][16]. It was confirmed that the GP zone was formed rapidly at a temperature of 120 °C, peaked within about 30 min of aging, and then transformed to η' and decreased.…”
Section: Alloy and Process Designmentioning
confidence: 92%
See 1 more Smart Citation
“…were performed under conditions of 470 °C/2 h of solution temperature and 120 °C of artificial aging, and, in order to learn more about the formation tendency of the GP zone, which is the nucleation site of the η' phase, the region between 0 and 1 h was enlarged and is shown in Figure 1. The heat treatment conditions used in the calculation were the commonly performed T6 heat treatment conditions for Al-Mg-Zn-Cu-based aluminum alloys [14][15][16]. It was confirmed that the GP zone was formed rapidly at a temperature of 120 °C, peaked within about 30 min of aging, and then transformed to η' and decreased.…”
Section: Alloy and Process Designmentioning
confidence: 92%
“…Therefore, currently, Al-Mg-Si alloys are mainly used, which have high formability and relatively low yield strength, even after natural aging, and excellent bakehardening characteristics after paint bake treatment. On the other hand, in the case of Al-Mg-Zn-Cu alloys, it is generally known that maximum strength is obtained through artificial aging at a temperature of around 120 • C [14][15][16], and excellent mechanical properties of over 500 MPa can be secured [17,18]. But, despite their high-strength characteristics, they are not preferred due to increased yield strength due to natural aging, increased sheet-forming pressure, and reduced mechanical properties due to grain coarsening at bake-hardening temperatures [7,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%